Effect of e‐cigarette advertisement themes on hypothetical e‐cigarette purchasing in price‐responsive adolescents. (14th May 2020) - Barnes, Andrew J.; Bono, Rose S.; Rudy, Alyssa K.; Hoetger, Cosima; Nicksic, Nicole E.; Cobb, Caroline O.
Abstract: Aims: To examine the effect on adolescents of exposure to different e‐cigarette advertisement themes on reported likelihood of purchasing e‐cigarettes in a hypothetical scenario. Design: Between‐subjects design of four randomly assigned thematic conditions derived from a content analysis of 350 e‐cigarette advertisements: general, flavor‐ and taste‐themed, people‐ and product use‐themed or control advertisements for bottled water. Setting: Virginia, USA. Participants: Of 1360 adolescents (13–18 years old) participating, 1063 had complete data (519 current cigarette smokers, 544 tobacco‐susceptible non‐smokers). Measurements: Participants completed an e‐cigarette purchase task, reporting the likelihood of buying an e‐cigarette at various prices. Indices of abuse liability included price responsiveness (whether likelihood of purchase decreased with increasing prices) and, among price‐responsive adolescents, breakpoint (highest price before definitely would not buy), maximum probability‐weighted expenditure (Omax ) and price elasticity (how quickly willingness to purchase decreases as prices increase). Regressions controlled for demographics, prior tobacco ad exposure, tobacco/substance use and sensation‐seeking. Findings: Prior advertisement exposure was positively associated with being price‐responsive [odds ratio (OR) = 1.12, 95% confidence interval (CI) = 1.03, 1.22; P < 0.05]. Among price‐responsive adolescents ( n = 579), breakpoints were 58% higher in the flavor‐ and taste‐themed condition (β = 0.46, 95% CI = <0.01, 0.92) and 75% higher in the people‐ and product use‐themed condition (β = 0.56, 95% CI = 0.10, 1.03) compared with control ( P s < 0.05). Exposure to people‐ and product use‐themed advertisements was associated with a 60% higher Omax (β = 0.47, 95% CI = 0.01, 0.93; P < 0.05). The general and people‐ and product use‐themed conditions were associated with 19% (β = −0.21, 95% CI = –0.38, ‐0.04) and 21% (β = −0.24, 95% CI = –0.42, −0.06) lower elasticity, respectively ( P s < 0.05). Conclusions: E‐cigarette advertising exposure may increase reported likelihood of purchasing e‐cigarettes, with effects differing by advertisement content. People‐ and product use‐themed e‐cigarette advertisements increased reported likelihood of purchasing in price‐responsive adolescents.